If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 9 = 12x + 21 Reorder the terms: 9 + 16x = 12x + 21 Reorder the terms: 9 + 16x = 21 + 12x Solving 9 + 16x = 21 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 9 + 16x + -12x = 21 + 12x + -12x Combine like terms: 16x + -12x = 4x 9 + 4x = 21 + 12x + -12x Combine like terms: 12x + -12x = 0 9 + 4x = 21 + 0 9 + 4x = 21 Add '-9' to each side of the equation. 9 + -9 + 4x = 21 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 21 + -9 4x = 21 + -9 Combine like terms: 21 + -9 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 10n^2=n^2+16 | | 45x+85=300 | | 23+(-78)= | | -2(2y+3)+2=0 | | 16+2v+3v-9=6v+12-v-5 | | y+6.2=2.4 | | 5(8F)+4(9-F)+37= | | 0.1x/x=0.56 | | f(x)=x^2+3x-88 | | n^2-27n+168=0 | | 12-6x+4-x=3+8x+13-11x | | z^2-14z=-11 | | 6+5x=-7x+78 | | -23-3m=-20 | | 1/x=0.079461 | | 6(2x+1)=6-13x | | 54x+2x=1 | | 5(x+3)=5x-2 | | -6(n+3)=-6n+3(n-12) | | 3s-5=16 | | 6(2x+11)=6-13x | | Ab+bc+abc= | | 12(m-12)=6(1+7m) | | 6-5+10= | | -6(k+11)=6(k-5) | | x^2+12x=324 | | 4(x+-2)=3(1.5+x) | | 32+32x=-4(-8x+1) | | 6/7s=-1/6 | | (7x+1)+(5x-1)=180 | | -89=-3(-3v+4)-5 | | (x+y)(a+b)=0 |